PERGURUAN ISLAMIYAH SEBAGAI LEMBAGA PENDIDIKAN ISLAM TERTUA DI PONTIANAK - Ramadhan, Dendy; Hariansyah, Hariansyah; Wahab, Wahab (Universitas Islam Sultan Agung, 2019)
This article discusses an institution that has long existed and has a very important role in Pontianak. Beginning with the study conducted at the home of H. Arif until the establishment of an institution called